(untitled) (Revista de Biología Marina y Oceanografía, 2018)
Castillo & Pequeño (1998) dealt with the morphological differences between the species of Helcogrammoides genus, however, the distribution of the characters may obscure the quality of the diagnosis; therefore, to evaluate the morphological characters (morphometric and meristic) through multivariate and univariate statistical analysis can help in the description and morphological identification of the species. Here, we performed morphological analyses to improve the characterization of Helcogrammoides chilensis and H. cunninghami based on museum specimens and fresh material. Allometric correction allows a better discrimination between both Helcogrammoides species. Our results suggest new measures both morphometric and meristic for the diagnosis of Helcogrammoides.